The Influence Of Islamic Religious Education In Forming Discipline Character In Students At Medan State University - Laras Fitri Aini Hasibuan; Haliza Rahmania Putri; Hendriadi Hasibuan; Ratri Aulia Wijaya; Rama Ardiansyah Tumangger; Hapni Laila Siregar (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Islamic Religious Education (PAI) has become the most important part of the education curriculum in Indonesia, with the aim of increasing awareness and appreciation of the Islamic religion among the community, especially students. One of the most significant aspects influenced by PAI is the character of discipline. Discipline is the behavior of obeying rules and forming a series of behaviors, namely obedience, obedience, order and regularity. PAI can help students to know and appreciate matters related to discipline in Islam, as well as apply these principles on a daily basis. Therefore, this research was conducted to analyze the influence of Islamic Religious Education on the discipline of Medan State University students  The method used in this research is descriptive quantitative with data collection techniques through questionnaires. The research sample was 30 students selected using the Convenience Sampling technique. The types of data used are primary data and secondary data. The data analysis technique used is descriptive statistical analysis, namely percentage analysis. The results of the research show that the influence of Islamic religious education in forming disciplined character in students at Medan State University has role is important and has a significant influence in shaping students' disciplined character, so it needs to be optimized in the learning process at Medan State University.